Respuesta :

Answer:

[tex]S_n = \frac{3ab}{2 (b-a)}[/tex]

Step-by-step explanation:

The correct question is: If the first, second and last term of an AP are a,b and 2a respectively, then show that the sum of all terms of an AP is 3ab/2(b-a)​.

Firstly, as we know that the nth term of an A.P. is given by the following formula;

[tex]a_n=a+(n-1)d[/tex] ,  where a = first term of AP, d = common difference, n = number of terms in an AP and [tex]a_n[/tex] = last term

Since it is given that the first, second and last term of an AP are a,b and 2a respectively, that means;

first term = a

d = second term - first term = b - a

[tex]a_n[/tex] = 2a

So,  [tex]a_n=a+(n-1)d[/tex]

       [tex]2a=a+(n-1)(b-a)[/tex]

       [tex]2a-a=(n-1)(b-a)[/tex]

        [tex]a=(n-1)(b-a)[/tex]

        [tex]\frac{a}{b-a} = n - 1[/tex]

        [tex]\frac{a}{b-a} +1= n[/tex]

        [tex]\frac{a+(b-a)}{b-a} = n[/tex]

         [tex]n=\frac{b}{b-a}[/tex]    ------------- [equation 1]

Now, the formula for the sum to n terms of an AP when the last term is given to us is;

              [tex]S_n = \frac{n}{2}[\text{first term} + \text{last term}][/tex]

              [tex]S_n = \frac{b}{2\times (b-a)}[a +2a][/tex]      {using equation 1}

              [tex]S_n = \frac{b}{2 (b-a)}[3a][/tex]

              [tex]S_n = \frac{3ab}{2 (b-a)}[/tex]

Hence proved.